2022
DOI: 10.29210/167500
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of psychological capital on teachers’ organizational commitment through interpersonal communication

Abstract: This study explores the effect of psychological capital (PsyCap) on teachers' organizational commitment, mediated by interpersonal communication. The research data was collected by the questionnaire: PsyCap, interpersonal communication, and organizational commitment in a Likert scale model through the survey methods toward 303 teachers of State Junior High School in Indonesia. Data analysis uses path analysis supported by descriptive statistics and correlational. The results show that PsyCap affects teachers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Benefits for lecturers or teachers, this research makes it easier to determine the suitable learning media and models according to the needs and perceptions of students. The success of online learning also depends on the media and models applied (Gustari & Widodo, 2022;Staddon, 2022;Syahrastani, 2022). Thus, in general research, this perception brings many benefits both in terms of students, lecturers, and educational institutions and aims to improve the quality of education provided.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits for lecturers or teachers, this research makes it easier to determine the suitable learning media and models according to the needs and perceptions of students. The success of online learning also depends on the media and models applied (Gustari & Widodo, 2022;Staddon, 2022;Syahrastani, 2022). Thus, in general research, this perception brings many benefits both in terms of students, lecturers, and educational institutions and aims to improve the quality of education provided.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of the relationship between psychological capital and interpersonal interaction is actively discussed in modern psychology. In particular, I. Gustari and V. Widodo (Gustari & Widodo, 2022) found that psychological capital influences the organizational commitment of teachers (the desire to work in an organization and contribute to its success) through interpersonal communication. S. A. Usman with colleagues (Usman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%